Good and Effective EFL Teachers from the Perspectives of Secondary School Students in Bali: Gender-Based Study - Ni Putu Sutraningsih; Luh Putu Artini; Luh Gede Eka Wahyuni (Journal on Education, 2024)
This study was conducted in order to investigate the students’ perceptions about good and effective English teacher. Apart from that, it also aims to find out whether there are significant differences between male and female students in categorizing how English teachers can be called good and effective teachers. Descriptive qualitative research will be used to collect data. The subjects of this research were eighth-grade junior high school students at SMP Negeri 4 Petang. A total of 75 students were asked to fill out a self-range questionnaire and 20 students (10 female and 10 male) were appointed for the focus group discussion session. The results revealed female students' perceptions of good teachers who prioritize a fun and interesting learning atmosphere, while male students focused on a teacher who cares about all students. Both female and male students value a teacher who can make learning enjoyable and engaging, using ice-breaking activities and other interactive methods to maintain interest. However, in relation to the male and female students’ perception regarding effective teachers there were some differences in their preferences regarding teaching strategies and how to increasing motivation in learning. Male students think that the motivation provided by words does not affect their interest in learning English. They are more motivated while practicing directly. Meanwhile, for female students quotes really motivate them to learn English, in addition to other learning activities. Both female and male students value teachers who are well-prepared for their lessons and can manage their time effectively to ensure that the material is covered in a timely manner.